Psychological effects on ancestral rituals in Saraguro—Ecuador - Mónica Hinojosa Becerra; Mayra Adelina Rivas Paladines; Mónica Maldonado Espinosa (INFAD, 2020)
Our communication seeks to understand the influence of ancient healing rituals on mental health. We understand mental health as the welfare state that results from the balance between the person and their environment: social, emotional and cultural. This research focuses on the healing rituals with entheogenic substances practiced by the yachag or healers of the Saraguro nationality. The Saraguro nationality belongs to the 14 ethnic groups and indigenous nationalities identified in Ecuador. It is characterized by the secrecy between ancient wisdom and the Western Catholic religion. They understand the physical and spiritual individual as a unit, physical healing begins with the spirit, with the energy of life. For the yachag the mother plant is the aguacoya or san pedro. Healing with aguacoya is performed with a ritual that lasts one night. The effects produced by the consumption of the plant are: physiological, visions and sensorial and affective disinhibition. From the studies of personality and mental health, we have set out to analyze the relationship of the individual with the healing and healing processes. We take Erikson’s hierarchical stages as a theoretical reference, from which the development of life is proposed in eight stages that face social realities in function of the Ego. We participated for two years in ritual sanctions with aguacoya, observing the process of personal change of 27 randomly selected participants. We analyze the influence of ritual, integrating the levels: somatic, psychic and social-ethical; understanding these levels in relation to Erikson from the unresolved conflicts in each of the stages of life. There is a psychological typology that predisposes individuals to participate in rituals and a series of personality traits that influence the individual to find healing by overcoming unresolved conflicts through ritual.